Breed and selection line differences in the temperament of beef cattle - doi: 10.4025/actascianimsci.v35i2.16426 - Piovezan, Ubiratan; Cyrillo, Joslaine Noely dos Santos Gonçalves; Costa, Mateus José Rodrigues Paranhos da (Acta Scientiarum. Animal Sciences, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> The temperament of four beef cattle breeds were measured using a flight time test (FT) and a behavior score test (BST). FT was defined as the time taken by animals to cross a distance of 2 m after weight scale. The BST used a visual assessment of cattle behavior in which the results of four categories defined the score: movements, breathing intensity, vocalization and kicking. FT and BST coefficients of heritability were estimated using the restricted maximum likelihood, considering half siblings. Caracu presented a lower BST value than the other breeds. Nellore presented intermediate results, followed by Guzerat and Gyr with similar and higher means (p < 0.05). Similar results were observed with FT, but Caracu and Nellore did not differ from each other. A low association between FT and BST was found (rp= -0.36; p < 0.01). The correlation between a sire’s ranking, according to the predicted breeding values (p) estimated for FT and BST, was moderate and negative (rs = -0.63; p < 0.001). Heritability estimates for FT and BST were 0.35 and 0.34, respectively. Inside Nellore breed, herds with different selection criteria for weight were compared. Our results show that selection line based on weight might positively modulate temperament of Bos indicus cattle.